Binge eating disorder: before and after bariatric surgery - Corrêa, Renata Queiroz (2021)
Bariatric surgery plays an important role in the treatment of obesity, however, it may be interfered with by psychopathological characteristics such as binge eating, which may be associated with adverse surgical outcomes, interfering with weight loss. Objective: to analyze the clinical and epidemiological profile of patients with binge eating before and after undergoing bariatric surgery, evaluating the influence of this procedure on this pathology. Methodology: cross-sectional, retrospective, survey-type study, carried out between 2020-2021. Sample composed of 5,160 individuals who underwent bariatric surgery, regardless of time, from any region of Brazil. Results: of 5,160 participants, 52.1% did not have and did not develop binge eating, 9.2% had and remained, 36.2% had and improved and 2.3% did not have and developed. There was a predominance: women, median age between 31 and 44 years, southeast region, whites, complete higher education and married. Physical activity was less performed among patients with binge eating, as well as psychological follow-up before surgery. Weight, BMI and time of surgical performance were higher in patients with compulsion and gastric bypass was the most prevalent type. Psychiatric comorbidities were more common among binge patients. Conclusion: binge eating interfered in the results of bariatric surgery, leading to less weight loss or maintenance, obesity permanence and worsening of psychiatric comorbidities. It is necessary to recognize the development and maintenance factors of binge eating to develop strategies to improve surgical outcomes and quality of life in this population.